YAP activation promotes the transdifferentiation of cardiac fibroblasts to myofibroblasts in matrix remodeling of dilated cardiomyopathy - Jin,Bo (2019)
Yes-associated protein (YAP) is an important regulator of cellular proliferation and transdifferentiation. However, little is known about the mechanisms underlying myofibroblast transdifferentiation in dilated cardiomyopathy (DCM). We investigated the role of YAP in the pathological process of cardiac matrix remodeling. A classic model of DCM was established in BALB/c mice by immunization with porcine cardiac myosin. Cardiac fibroblasts were isolated from neonatal Sprague-Dawley rats by density gradient centrifugation. The expression levels of α-smooth muscle actin (α-SMA) and collagen volume fraction (CVF) were significantly increased in DCM mice. Angiotensin II (Ang II)-mediated YAP activation promoted the proliferation and transdifferentiation of neonatal rat cardiac fibroblasts, and this effect was significantly suppressed in the shRNA YAP + Ang II group compared with the shRNA Control + Ang II group in vitro (2.98±0.34 ×105 vs 5.52±0.82 ×105, P<0.01). Inhibition of endogenous Ang II-stimulated YAP improved the cardiac function by targeting myofibroblast transdifferentiation to attenuate matrix remodeling in vivo. In the valsartan group, left ventricular ejection fraction and fractional shortening were significantly increased compared with the DCM group (52.72±5.51% vs 44.46±3.01%, P<0.05; 34.84±3.85% vs 26.65±3.12%, P<0.01). Our study demonstrated that YAP was a regulator of cardiac myofibroblast differentiation, and regulation of YAP signaling pathway contributed to improve cardiac function of DCM mice, possibly in part by decreasing myofibroblast transdifferentiation to inhibit matrix remodeling.